An exploration of possible mechanisms underlying the beneficial effects of enriched rehabilitation on post-stroke recovery of function - Clarke, Jared, 1979- (2010)
Thesis (Ph.D.)--Memorial University of Newfoundland, 2010. Medicine Includes bibliographical references A combination of enriched environment and daily reaching therapy (i.e. enriched rehabilitation) enhances functional recovery following focal ischemia in rats. However, the mechanisms contributing to recovery, and potentially critical influence of timing of rehabilitation, remain unclear. Enriched rehabilitation is especially effective when initiated early, however the mechanisms underlying this critical time window have not been determined. Chapter 2 examined the effects of early rehabilitation on neuronal activation (FosB/ΔFosB), delayed cell death (Fluoro Jade C) and inflammation (ED-1) following endothelin-1 induced focal ischemia. Enriched rehabilitation increased the activity of perilesional cortex in the early post-stroke treatment period. This increased activity likely contributes to the neuroplastic changes and functional recovery observed with extended periods of rehabilitation. Importantly, enriched environment alone did not lead to enhanced activity suggesting that task-specific rehabilitation is necessary to promote maximal recovery. Changes in FosB/ΔFosB expression provide a powerful approach for detecting use-dependent recovery of function following stroke or brain injury. Most recovery tends to occur early after stroke, while improvement in the chronic phase is limited. Chapter 3 examined the effects of periodic returns to therapy in the chronic phase of recovery following focal ischemia. Ischemic rats were treated for nine weeks with enriched rehabilitation, then returned for two periods of intensive "tune-up" therapy. Functional outcome was assessed throughout the treatment period, and neuroplastic changes were measured at the end of the study using Golgi-Cox analysis. While early rehabilitation provided enhanced recovery in both reaching and foot placement ability, there was little benefit of more chronic phases of treatment. Chapter 4 shows that enriched environment has differential effects on recovery of skilled and unskilled motor functions after focal ischemia. Ischemic rats exposed to longer daily periods of enrichment, in combination with reach therapy, showed greater improvement in reaching ability compared to those receiving less exposure to enrichment. However, all groups showed similar recovery in foot placement and forelimb use, suggesting that even short durations of enriched environment are sufficient to promote recovery of unskilled motor functions. The synergistic effect of enrichment and task-specific therapy provides further evidence that stimulating environments should be incorporated into rehabilitation programs.